Repetition of sound, structure and meaning: a study of poeticised English-Chinese advertisement translation - Ying Cui; Yanli Zhao (JoSTrans: The Journal of Specialised Translation)
Advertisement translation is highly creative, and poeticising is one type of flexible approach, which is prominent in English-Chinese advertisement translation. There are studies on the poetic textual devices in Chinese and English advertisements, but research is rare regarding the strategy of poeticising in English-Chinese advertisement translation. This investigation studies a corpus of 146 English advertisements translated into Chinese and analyzes the specific examples of poeticising. Poeticising in Chinese translations is mainly realised via the use of repetition, including the repetition of sound, the repetition of structure, and the repetition of semantic meaning. The application of repetition in advertisements helps enhance the poetic essence of advertisements, appeal to readers' aesthetic needs, arouse their interest, increase the impact on the reader, and serve the final goal of promotion. Discussion of the strategies and effects of poeticising is intended to provide a point of reference for translators, concerning the value of being creative in advertisement translation and enhancing the poetical quality of the translations, as well as the Chinese linguistic and cultural characteristics.